2023
DOI: 10.1021/jacs.3c05342
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Second Sphere Residue Tunes Copper Site Reactivity in Lytic Polysaccharide Monooxygenases

Kelsi R. Hall,
Chris Joseph,
Iván Ayuso-Fernández
et al.

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are powerful monocopper enzymes that can activate strong C–H bonds through a mechanism that remains largely unknown. Herein, we investigated the role of a conserved glutamine/glutamate in the second coordination sphere. Mutation of the Gln in NcAA9C to Glu, Asp, or Asn showed that the nature and distance of the headgroup to the copper fine-tune LPMO functionality and copper reactivity. The presence of Glu or Asp close to the copper lowered the reduction potential and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 105 publications
(287 reference statements)
3
15
0
Order By: Relevance
“…In contrast, the second-order rate constant for the reoxidation of NcAA9C−Cu(I) shows no pHdependency (Figure S20). Notably, the obtained second-order rate constants for reduction and reoxidation at pH 7.0 are in line with data reported by Hall et al 43 The fast kinetic data are in accord with the pH-dependency of half-saturating ascorbate concentrations derived from steady-state analysis (Figure 4C and Table S10). After finding that the ascorbic acid/ascorbate concentration necessary to reach half-maximal activity is ∼50-fold higher at pH 4.0 than at pH 7.0 (890 and 17 μM, respectively), a reassessment of the pH profile using increased ascorbate concentrations showed essentially no pH-dependency of LPMO activity between pH 4.0 and 6.0 (TN = 30−35 s −1 ), while activity still increases with pH from 6.0 to 8.0 (TN = 35−55 s −1 ) (Figure 4A).…”
Section: T H Isupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the second-order rate constant for the reoxidation of NcAA9C−Cu(I) shows no pHdependency (Figure S20). Notably, the obtained second-order rate constants for reduction and reoxidation at pH 7.0 are in line with data reported by Hall et al 43 The fast kinetic data are in accord with the pH-dependency of half-saturating ascorbate concentrations derived from steady-state analysis (Figure 4C and Table S10). After finding that the ascorbic acid/ascorbate concentration necessary to reach half-maximal activity is ∼50-fold higher at pH 4.0 than at pH 7.0 (890 and 17 μM, respectively), a reassessment of the pH profile using increased ascorbate concentrations showed essentially no pH-dependency of LPMO activity between pH 4.0 and 6.0 (TN = 30−35 s −1 ), while activity still increases with pH from 6.0 to 8.0 (TN = 35−55 s −1 ) (Figure 4A).…”
Section: T H Isupporting
confidence: 91%
“…In contrast, the second-order rate constant for the reoxidation of Nc AA9C–Cu­(I) shows no pH-dependency (Figure S20). Notably, the obtained second-order rate constants for reduction and reoxidation at pH 7.0 are in line with data reported by Hall et al…”
Section: Resultsmentioning
confidence: 92%
“…The increased oxidase activity that results from the Q219E mutation at position 2 relies on the presence of a tyrosine at position 3, and future studies should aim to uncover the relationship between these two residues. Interestingly, the interplay between residues at positions 2 and 3 could couple the variation at position 2 to possible protective hole hopping mechanisms mediated by a tyrosine at position 3, ,, as recently shown for a cellulose-active AA9 LPMO carrying the HQY motif . On a related note, the presence of a tyrosine at position 3 and glutamate at position 2 does not exist naturally in AA10 LPMOs but is the most prevalent combination in (chitin-active) LPMOs in the AA11 family.…”
Section: Discussionmentioning
confidence: 75%
“…Another conserved second sphere residue is a glutamine or glutamate residue, which typically coexists with an axial tyrosine or phenylalanine, respectively, in AA9 and AA10 LPMOs. This glutamine/glutamate residue has been shown to play a crucial role in the peroxygenase reaction through constraining and orienting H 2 O 2 and subsequent reactive intermediates. ,, Mutagenesis studies have confirmed this, along with an additional role in controlling copper reactivity. , Alongside the glutamine in AA9s, a conserved histidine residue has also been predicted to play a role in positioning oxygen species and has a debated role as a proton donor. , …”
Section: Introductionmentioning
confidence: 97%
“…[7] DeBeer, Eijsink, Sørlie and coworkers have also recently reported that the protonation state of a conserved glutamine/glutamate residue on the secondary coordination sphere of the Cu active center might also play a critical role on controlling the oxidase, peroxidase and peroxygenase reactivity. [8] In the peroxygenase and peroxidase reactions, the proposed catalytic cycles are initiated by coordination of the H 2 O 2 to the Cu I ion, which is proposed to trigger an homolytic OÀ O bond cleavage to generate a Cu II OH core and hydroxyl radical (species G and H in Figure 1B). [9] In the peroxygenase cycle, the reaction between the CuOH core and the hydroxyl radical is proposed to generate the hydroxylating Cu-oxyl intermediate (species G to species E in Figure 1B), a reaction pathway supported by computations.…”
Section: Introductionmentioning
confidence: 99%